2016
DOI: 10.36331/revista.v3i1.22
|View full text |Cite
|
Sign up to set email alerts
|

Serological and Molecular Identification of Cucumber Mosaic Virus (Cmv) Infecting Banana Crops in Ecuador

Abstract: The serologic survey and the confirmatory molecular diagnostic suggested evidence of a fairly presence of ILT infection in the main poultry farms of Ecuador. The current work highlights the need to apply a control program of ILT based on vaccination and standard biosecurity measures in the poultry farms of Ecuador.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The positive reaction of all the virus isolates with cucumovirus polyclonal antiserum further affirmed they belong to the genus Cucumovirus.The production of 500 base pair amplicons using cucumovirus specific primers by all the virus isolates in this study further confirmed that they were all CMV isolates. Yeturu, et al [33] had reported the detection of CMV using cucumovirus specific primers with the resultant production of amplicons of 500 base pairs. Characterization and identification of plant viruses using gene sequence data has become the ultimate in recent times [34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…The positive reaction of all the virus isolates with cucumovirus polyclonal antiserum further affirmed they belong to the genus Cucumovirus.The production of 500 base pair amplicons using cucumovirus specific primers by all the virus isolates in this study further confirmed that they were all CMV isolates. Yeturu, et al [33] had reported the detection of CMV using cucumovirus specific primers with the resultant production of amplicons of 500 base pairs. Characterization and identification of plant viruses using gene sequence data has become the ultimate in recent times [34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Mosaic patterns or discontinuous linear streaking bands, extending from leaf margin to midrib are the characteristic symptoms of infectious chlorosis. Curling of leaves, rosette appearance of leaf arrangement and dead or dying suckersare noticed in advanced cases (Niblett et al, 1994;Rodoni et al, 1997;Sivaprasad et al, 2016;Tripathy, 2016). Banana mosaic is categorised as cosmopolitan and is found wherever bananas are grown.…”
Section: Symptoms Developed By the Virusmentioning
confidence: 99%
“…Cucumber mosaic virus isolates were phylogenetically analysed and the subgroup I have subdivided into IA and IB. Among the subgroups, subgroup 1B of CMV is limited to Asia, and the other two subgroups (i.e., 1A and 2) are distributed worldwide (Sivaprasad et al, 2016).…”
Section: Distribution Of the Virusmentioning
confidence: 99%